US President Warms Up as Genome Tempers Cool (The Scientific World Journal, 2001)
Nature leads this week with a story about hints that the Bush administration may be softening its position on global warming. Science kicks off with a story about how an effort to sequence the rat genome makes for strange bedfellows.